National culture as a moderator in ambidexterity-performance relationships: a meta-analysis - Lim, E.; António, N. S. (International Journal of Business Innovation and Research, 2020)
This meta-analysis uses 44 existing studies conducted in single-nation contexts (k=44), constituting an aggregate sample of 20,886 observations (N=20,886), to assess the potential moderating role of national culture on organisational ambidexterity- performance relationships. The results indicate an overall positive ambidexterity-performance link, which is stronger in countries with low levels of institutional collectivism, high levels of in-group collectivism, low levels of future orientation, low levels of performance orientation, and low levels of uncertainty avoidance. Additionally, counter to expectation, results suggest that the ambidexterity-performance relationship is stronger in countries with high levels of power distance.